2021
DOI: 10.1186/s12889-021-12123-7
|View full text |Cite
|
Sign up to set email alerts
|

The rural Uganda non-communicable disease (RUNCD) study: prevalence and risk factors of self-reported NCDs from a cross sectional survey

Abstract: Background Non-communicable diseases (NCDs) are an increasing global concern, with morbidity and mortality largely occurring in low- and middle-income settings. We established the prospective Rural Uganda Non-Communicable Disease (RUNCD) cohort to longitudinally characterize the NCD prevalence, progression, and complications in rural Africa. Methods We conducted a population-based census for NCD research. We systematically enrolled adults in each h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
0
16
1
Order By: Relevance
“…When we compare our findings with reports from other countries, we uncover a wide range of outcomes. A cross-sectional survey conducted in Nakaseke health district in Uganda reported a quite similar prevalence rate of self-reported high blood pressure at 6.3% [26]. Population-based studies among women in Kenya and Benin reported prevalence rates of 9.38% and 9.9%, respectively [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…When we compare our findings with reports from other countries, we uncover a wide range of outcomes. A cross-sectional survey conducted in Nakaseke health district in Uganda reported a quite similar prevalence rate of self-reported high blood pressure at 6.3% [26]. Population-based studies among women in Kenya and Benin reported prevalence rates of 9.38% and 9.9%, respectively [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Uganda faces a budding epidemic of hypertension. In 2015, the prevalence of hypertension was 26.4%, and the condition remains undiagnosed and undetected in many people (9). A study conducted in 1 district in central Uganda reported that 6.3% of people in Uganda self-reported having hypertension (10).…”
Section: Introductionmentioning
confidence: 99%
“…The available information on hypertension in Uganda in the scientific literature mostly describes the proportion of people at risk for hypertension and those who have hypertension (9)(10)(11). Few published studies focus on the status of hypertension diagnostic services available in Uganda and the readiness of health facilities to offer hypertension care (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the UNAIDS report, antiretroviral treatment coverage in Uganda is at 90% [ 13 ]. The growing number of persons living with chronic illnesses especially NCDs is on the rise in many developing nations [ 14 ]. HIV/AIDS has joined the list of chronic illnesses because many PLWHIV can now live longer with the virus because of the life-saving medicines [ 15 ].…”
Section: Introductionmentioning
confidence: 99%